Plasmon-free SERS detection of environmental CO2 on TiO2 surfaces. Issue 6 (21st January 2016) - Bontempi, Nicolò; Carletti, Luca; De Angelis, Costantino; Alessandri, Ivano
Abstract : SiO2 /TiO2 core/shell beads exploit light trapping and morphology dependent resonances to detect CO2 adsorbed on TiO2 surfaces. Abstract : SiO2 /TiO2 core/shell beads (T-rex) were designed, fabricated and tested for Raman detection of environmental CO2 under real-working conditions, as those encountered, for example, in solar-to-fuel conversion reactions. The exploitation of light trapping and morphology dependent resonances was crucial for extending the limit of detection of CO2 adsorbed on TiO2 surfaces. T-rex beads allowed for achieving surface enhanced Raman scattering (SERS) without using plasmonic metals showing high-efficiency, fast response and reproducibility in CO2 detection in both air and solvents. The dependence of SERS activity on Mie-type resonances was investigated through a systematic comparison of experimental data and numerical simulations, demonstrating that T-rex beads can be tailored for the detection of gaseous environmental pollutants on the basis of simple, Mie-scattering based calculations. Three-dimensional T-rex colloidal crystals were also successfully tested in precise, in situ, real time detection of CO2 as a function of different temperature-sweep cycles.